SENTENCE (Modern education and development, 2025)
This article examines the concept of a sentence in English, focusing on its structure, types, and syntactic functions. A sentence, being the fundamental unit of communication in any language, plays a crucial role in conveying meaning. The study explores the grammatical components of a sentence, including subjects, predicates, and complements, and categorizes different types of sentences based on their functions and structures. Through this analysis, the article highlights the importance of sentence formation in effective communication and language learning.